A Coupled Model for Two-Phase Simulation of a Heavy Water Pressure Vessel Reactor - Ramajo, Damian Enrique (2015)
A Multi-dimensional computational fluid dynamics(CFD) two-phase model was developed with the aim to simulatethe in-core coolant circuit of a pressurized heavy water reactor(PHWR) of a commercial nuclear power plant (NPP). Due to thefact that this PHWR is a Reactor Pressure Vessel type (RPV),three-dimensional (3D) detailed modelling of the large reservoirs ofthe RPV (the upper and lower plenums and the downcomer) werecoupled with an in-house finite volume one-dimensional (1D) codein order to model the 451 coolant channels housing the nuclear fuel.Regarding the 1D code, suitable empirical correlations for taking intoaccount the in-channel distributed (friction losses) and concentrated(spacer grids, inlet and outlet throttles) pressure losses were used.A local power distribution at each one of the coolant channelswas also taken into account. The heat transfer between the coolantand the surrounding moderator was accurately calculated using atwo-dimensional theoretical model. The implementation of subcooledboiling and condensation models in the 1D code along with the useof functions for representing the thermal and dynamic properties ofthe coolant and moderator (heavy water) allow to have estimationsof the in-core steam generation under nominal flow conditions for ageneric fission power distribution. The in-core mass flow distributionresults for steady state nominal conditions are in agreement with theexpected from design, thus getting a first assessment of the coupled1/3D model. Results for nominal condition were compared withthose obtained with a previous 1/3D single-phase model getting morerealistic temperature patterns, also allowing visualize low values ofvoid fraction inside the upper plenum. It must be mentioned that thecurrent results were obtained by imposing prescribed fission powerfunctions from literature. Therefore, results are showed with the aimof point out the potentiality of the developed model.